Hierarchical porous N-doped graphene aerogel with good wettability for high-performance ionic liquid-based supercapacitors. (10th January 2021) - Chen, Yujuan; Jiang, Yuyang; Liu, Zhaoen; Yang, Lifang; Du, Quanzhou; Zhuo, Kelei
Highlights: Phenolic hydroxyl groups on the graphene surface are successfully protected. The as-prepared material has good wettability with ionic liquid electrolyte. Urea phosphate as both the nitrogen dopant and hydroxyl group protector. Symmetric supercapacitor provides an excellent energy density of 97.2 Wh kg −1 . Abstract: The improvement of the wettability between electrode materials and ionic liquid electrolytes is critical to increase the performance of electrode materials for supercapacitors. Herein, we demonstrate the synthesis of a urea phosphate-derived graphene aerogel (UPGA) with good wettability by one-step hydrothermal treatment using graphene oxide (GO) as the precursor and urea phosphate (UP) as both the nitrogen dopant and hydroxyl group protector. The as-obtained UPGA has appropriate doped-N atoms, unique hierarchical porous structure, and good wettability by 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4 ) ionic liquid. The UPGA displays a high specific capacitance of 196.7 F g −1 at 1 A g −1 . Moreover, a symmetrical UPGA-based supercapacitor delivers an excellent energy density of 97.2 Wh kg −1 at a power density of 0.9 kW kg −1 and a good cycling stability with the capacitance retention of 78.3% after 5500 cycles at 1 A g −1 . Therefore, the UPGA exhibits great potential in supercapacitor as electrode material. Graphical abstract: Image, graphical abstract